TOWARDS A CONTEXTUAL MODEL OF SOCIAL REHABILITATION POLICY IMPLEMENTATION: Evidence from Women Involved in Prostitution in Banjarmasin City - Syafari, Muhammad Riduansyah; Maulidah, Maulidah; Putera, Roni Ekha (Department of Government, FISIP, Universitas Padjadjaran, 2026)
Rehabilitation policy relies heavily on local governments to manage the complex, underlying urban social dynamics. This research analysed the social rehabilitation policy implementation regarding women in prostitution as a form of urban poverty case study location being Banjarmasin City, about institutional capacity, local powers and inter-agency collaboration. This research used a descriptive qualitative approach, with data collection methods including in-depth interviews with social affairs officials, social workers (SWs), rehabilitation analysts, and beneficiaries; non-participant observations at Baiman Shelter; and document review. Thematic analysis was informed by policy implementation frameworks and street-level bureaucracy theory. Results show an implementation strategy characterized by reactiveness, with triggers flowing from enforcement rather than vision; scarce capacity within the institutions meant to deliver stability, while significant discretion at ground level skewed the policy process towards short-term social control and away from long-term empowerment. Interagency collaboration is largely informal, while gender-sensitive approaches have not been meaningfully integrated into program design. The paper contributes a contextual model of social rehabilitation policy implementation in which frontline discretion operates amid the ambivalences of reactive governance dynamics shaped by an inter-institutional environment, characterized by both institutional constraints and informal coordination. It shifts street-level bureaucracy theory by showing that discretion is not just individual but also structurally determined (by institutional and/or socio-political forces), directly impacting the effectiveness/trajectory of the restoration policy analyzed in urban governance.